2019
DOI: 10.2166/wrd.2019.046
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic-environmental effects of sponge city under different spatial scales

Abstract: The storm water management models were established at three spatial scales (large, medium, and small) based on a sponge city pilot area in China to explore the hydrological and environmental effects of rainfall conditions and development modes. Results showed the following. (1) Total runoff reduction rates increased from 26.7% to 53.9% for the rainfall event of a 2-year recurrence period as the scale increased. For 5-year and above recurrence periods, total runoff reduction rates were 19.5–49.4%. These rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, modelling current and future overland flows in urban contexts is becoming more sophisticated, in order to better represent the variable terrains and surfaces encountered in built environments, and interactions between surface and sub-surface drainage systems, and to account for the impacts of climate and land-use changes. This is essential because in cities, more elements and factors (e.g., rainfall intensity and frequency, variable infiltration, soil moisture conditions and surface roughness, and coincident floods involving pluvial, surface water, groundwater, and river sources) affect the urban water cycle [76]. Water engineers and managers increasingly run two-dimensional hydrologic and hydraulic models (e.g., MIKE-URBAN, MIKE-SWMM, STORM, SWMM, UCURM, ILLUDAS, TRRL, SUSTAIN, MOUSE, and InfoWorks) to simulate complex urban water processes and map potential inundation extents and flood risks [77].…”
Section: Technology and Modelling Capabilitiesmentioning
confidence: 99%
“…However, modelling current and future overland flows in urban contexts is becoming more sophisticated, in order to better represent the variable terrains and surfaces encountered in built environments, and interactions between surface and sub-surface drainage systems, and to account for the impacts of climate and land-use changes. This is essential because in cities, more elements and factors (e.g., rainfall intensity and frequency, variable infiltration, soil moisture conditions and surface roughness, and coincident floods involving pluvial, surface water, groundwater, and river sources) affect the urban water cycle [76]. Water engineers and managers increasingly run two-dimensional hydrologic and hydraulic models (e.g., MIKE-URBAN, MIKE-SWMM, STORM, SWMM, UCURM, ILLUDAS, TRRL, SUSTAIN, MOUSE, and InfoWorks) to simulate complex urban water processes and map potential inundation extents and flood risks [77].…”
Section: Technology and Modelling Capabilitiesmentioning
confidence: 99%
“…Rainwater gardens, grass ditches, biological retention ponds, and other sunken green spaces were transformed to improve the rainwater storage capacity of the surface [37]. With the increase of the rainfall return period, the proportion of surface runoff increased, but the increase of the proportion of surface runoff after reconstruction was less than that before the reconstruction, which indicated that the reconstruction of the sponge plot had a certain reduction effect on surface runoff [38], and from 3 years to 50 years, the reduction rate of surface runoff increased from 37.73% to 47.43%. The improvement rate of the rainfall infiltration also increased from 23.36% to 39.36%.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the composite runoff coefficient has become a key factor in calculating the total annual runoff control rate, reflecting the influence of physical geographic elements in the basin on the relationship between precipitation and runoff [91,161]. It is used to calculate infiltration control indicators, determine the total annual runoff control rate, and formulate low impact, which become the prerequisite and basis for the development scale (LID) plan and the comprehensive optimization management decision of stormwater [92,162].…”
Section: Selected Pilot Citiesmentioning
confidence: 99%